A rapid biofabrication technique for self-assembled collagen-based multicellular and heterogeneous 3D tissue constructs. (1st July 2019) - Shahin-Shamsabadi, Alireza; Selvaganapathy, P. Ravi
Graphical abstract: Abstract: Although monolayer cell culture models are considered as gold standard for in vitro modeling of pathophysiological events, they cannot reconstruct in vivo like gradient of gases and nutrients and lack proper cell-cell and cell-matrix interactions. Spherical cellular aggregates, otherwise known as multicellular spheroids, are widely used as three-dimensional in vitro models to mimic natural in vivo cellular microenvironment for applications such as drug screening. Although very useful, the previously established techniques are limited to low cell numbers, their processes are usually slow, and sometimes show limitations in terms of the cell type that can be used. Here, a versatile technique based on rapid self-assembly of cells and extracellular matrix material in different shapes using microfabricated molds is introduced to form multicellular tissue constructs. The self-assembly process takes less than 6 h and produces a mechanically robust tissue construct that could be handled easily. We demonstrate that a variety of shapes including spherical, cuboidal, dumbbell- and cross-like shapes could be fabricated using this approach. Interestingly, the structures formed with non-spherical shapes were able to retain that shape even after removal from the molds and during long term cell culture. This versatile approach is applicable to a variety of cell types (breast cancer cell lines MCF-7, MDA-MB-321, Hs-578T; osteosarcoma cell line SaOS-2; endothelial cell line HUVEC) as well as a range of cell numbers (10 4 –10 6 ). Furthermore, we also show that the constructs could be spatially patterned to position various cell types in a precisely controlled way. Such heterogeneous constructs that are formed provide physiologically relevant cell densities, 3D structure as well as close positioning of multiple types of cells that are not possible using other fabrication approaches. This fabrication approach will find significant applications in developing 3D cell culture models for drug discovery as well as tissue grafts for implantation. Statement of Significance: In this manuscript we describe a method for rapid formation of tissue constructs (6 h as opposed to several days for current state of art methods). We also identify the essential factors needed for such a rapid consolidation into a construct. We demonstrate the ability to form non-spherical constructs of various shapes that retain their shape over long term as opposed to those formed with current state of art that lose their shape during long time cell culture. We also show the ability to form precise heterogeneous constructs consisting of multiple cell types and with well-defined interfaces that are not possible with current state of art methods. This method could be used with a wide variety of cell types and are mechanically robust within 6 h to be handled with tweezers. We believe that such multicellular, heterogeneous constructs would be of significant use to biologists and drug discovery researchers investigating mechanisms involved in diseases processes or the effect of drug on them.